The Concept of Insurable Interest - Das, Amruta (International Journal of Psychosocial Rehabilitation, 2025)
This research paper discusses the concept of Insurable Interest which is crucial to the insurance claims as it says that insurance can only be claimed by a person who has a vested interest in the subject matter of the insurance. The paper discusses the nature and types of insurance which are contractual and statutory. The paper elucidates the position of insurable interest when the subject matter is the life of an individual and discusses the concept in relation to husband and wife, parents and children, debtor and creditor & husband and wife. The paper concludes with talking about the need of doing away with Insurable interest in cases of life insurance.